Internuclear Ophthalmoplegia Secondary to Cocaine Abuse - Richard L. Rabin; Azeem Wasay; Nicolas Biro; Marcelle Morcos (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of internuclear ophthalmoplegia (INO) caused by cocaine. Method. We report a case of a 54-year-old female who presented with a left INO three days after snorting cocaine, and we review the literature. Results. MRI of the brain demonstrated several small abnormal foci in the pons on FLAIR and diffusion weighted imaging consistent with ischemic infarction. The patient’s symptoms remained stable throughout her hospitalization. She was sent to a rehabilitation facility and was lost to follow-up. Conclusion. In cases of extraocular movement abnormalities, it is important to inquire about recreational drug use.